2012
DOI: 10.1016/j.neuroimage.2011.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Multi-region analysis of longitudinal FDG-PET for the classification of Alzheimer's disease

Abstract: Imaging biomarkers for Alzheimer’s disease are desirable for improved diagnosis and monitoring, as well as drug discovery. Automated image-based classification of individual patients could provide valuable diagnostic support for clinicians, when considered alongside cognitive assessment scores. We investigate the value of combining cross-sectional and longitudinal multi-region FDG-PET information for classification, using clinical and imaging data from the Alzheimer’s Disease Neuroimaging Initiative. Whole-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 50 publications
(74 reference statements)
5
94
0
3
Order By: Relevance
“…This observation confirms the utility of such data-driven methodology to uncover correlations that have pathophysiologic meaning (Table 3). Several studies have implemented automated image-based classification methods to differentiate AD and MCI patients from controls and have found such methods to have a statistical accuracy of 90% in discriminating AD patients from controls (25)(26)(27). When MCI patients who later converted to AD were investigated by unimodal biomarkers, the reported ability to discriminate from controls ranged from 80% (28) to 91% (29).…”
Section: Discussionmentioning
confidence: 99%
“…This observation confirms the utility of such data-driven methodology to uncover correlations that have pathophysiologic meaning (Table 3). Several studies have implemented automated image-based classification methods to differentiate AD and MCI patients from controls and have found such methods to have a statistical accuracy of 90% in discriminating AD patients from controls (25)(26)(27). When MCI patients who later converted to AD were investigated by unimodal biomarkers, the reported ability to discriminate from controls ranged from 80% (28) to 91% (29).…”
Section: Discussionmentioning
confidence: 99%
“…Mormino et al used 11 C-PiB PET imaging to deduce a cutoff point to optimally separate PiB-positive from PiB-negative MCI patients, and found that PiB-positive MCI patients had lower hippocampal volumes and greater episodic memory loss compared with MCI patients with 11 C-PiB levels below the cutoff point of 1.465. The addition of longitudinal data to baseline data to improve classification accuracy from anatomically selected features of FDG-PET scans was the approach taken by Gray et al [285]. Across all categories, improved classification accuracies were reported, ranging from 65% in the MCI converter versus non-converter classification to 88% in discriminating between control and AD patients (Table 8).…”
Section: Studies Of the Adni Cohortmentioning
confidence: 99%
“…Arterial spin labeling (ASL) MRI is a non-invasive, rapid and increasingly widely available method for quantifying CBF; ASL represents a potential alternative modality for measuring brain perfusion as compared to positron emission tomography (PET) [12][13][14] that may facilitate routine clinical application in the work-up of dementia. AD-associated perfusion changes measured by ASL are strongly correlated with glucose metabolism alterations as measured by PET [9,15,16].…”
Section: Introductionmentioning
confidence: 99%